Enhancing the effectiveness of calculation of parameters for short circuit of threephase transformers using field simulation methods - Yarymbash, Dmytro; Yarymbash, Serhiy; Kotsur, Mykhailo; Divchuk, Tetyana (Eastern-European Journal of Enterprise Technologies, 2018)
We conducted theoretical research into electromagnetic processes when testing power transformers under the mode of the test short circuit based on a three-dimensional model of the magnetic field in the frequency statement. Reliability and accuracy of determining the parameters for the test short circuit of the power transformer for frequency-domain statements were substantiated with the use of verification of the data of calculation of frequency-domain and time dependent models of the magnetic field for frequency statements. The main regularities of the magnetic field distribution in the volume of the active part of the transformer were determined. In the magnetic field localization zones, 3D intensity distribution is uniform and is determined by the 2D distribution in the horizontal cross section of the active part in the middle of the phase windings height. The values of the axial component of the magnetic field intensity approach 96–97 % of the intensity vector module. An effective approach to field modeling was implemented based on decomposition of the computational domain into spatial zones. Each calculation zone is put in compliance with an electrical circuit of the substitution scheme. Distribution of electric potentials in the horizontal cross-sections of the conductors between the coils or between the turns of windings was accepted as uniform. The superposition of magnetic fields in spatial zones was implemented by means of dynamic synthesis by the criteria of minimal current error for electric circuits of the substitution scheme. The decomposition of the 3D area of field simulation area into the central and end zones is implemented at a distance of 10–15 % of the height of the phase windings, which ensures high accuracy of the magnetic field calculation with the error not exceeding 1.62 %. Time consumption for field simulation of electromagnetic processes under the mode of the test short circuit decreased by 5 times and requirements for the capacity of computing hardware resources decreased by 4 times. High accuracy of identification of parameters of the test short circuit of three-phase transformers was proved by comparing the calculation data to the results of tests at the private company "Eltiz" (Zaporizhzhia, Ukraine). Calculation errors do not exceed 1.42 % for active losses and 1.39 % for short circuit voltage. The proposed approach with the use of the methods of decomposition and of dynamic synthesis makes it possible to significantly improve the effectiveness of the preliminary stage of design preparation of production and can be used for solving the problems of design solutions optimization